2012
DOI: 10.1007/s12250-012-3244-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on factors related to rabies epidemic in China from 2007–2011

Abstract: To analyze features of the rabies epidemic in China between 2007 and 2011, identify factors influencing the epidemic and to provide a scientific basis for further control and prevention of rabies, Descriptive epidemiological methods and statistical analysis was used on data collected from the National Disease Reporting Information System between 2007 to 2011 and the National Active Surveillance System between 2007 and 2010. Our analysis shows that while the number of human rabies cases decreased year by year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 2 publications
8
44
0
4
Order By: Relevance
“…In Four-Year Retrospective Study by Teklu et al (2017) in Northwestern Tigray the incidence of human rabies exposure cases calculated per 100,000 populations was 35.8, 63.0, 89.8 and 73.1 in 2012, 2013, 2014 and 2015, respectively. The proximity of the site of the virus entry to the CNS increases the likelihood of a short incubation period (Yin et al, 2012). Following the bite of rabid animal the incubation period varies from 5 days to several years (usually 2 to 3 months; rarely more than 1 year) depending on the amount of virus in the inoculum, the density of motor endplates at the wound site and the proximity of virus entry to the central nervous system (WHO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Four-Year Retrospective Study by Teklu et al (2017) in Northwestern Tigray the incidence of human rabies exposure cases calculated per 100,000 populations was 35.8, 63.0, 89.8 and 73.1 in 2012, 2013, 2014 and 2015, respectively. The proximity of the site of the virus entry to the CNS increases the likelihood of a short incubation period (Yin et al, 2012). Following the bite of rabid animal the incubation period varies from 5 days to several years (usually 2 to 3 months; rarely more than 1 year) depending on the amount of virus in the inoculum, the density of motor endplates at the wound site and the proximity of virus entry to the central nervous system (WHO, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Data issued by the Chinese Center for Disease Control and Prevention showed that the incidence of rabies was 0.1058 per million population, with 1,425 deaths attributable to rabies in 2012. Within China, the three provinces with the highest incidence of rabies were Guangxi, Guizhou, and Hainan, with 0.4995, 0.3257, and 0.3077 cases/million, respectively (3,7). The 2012 Chinese Yearbook of Health Statistics revealed that, in 2011, rabies was the fourth most common cause of death among category A and B notifiable infectious diseases, following AIDS, infant tetanus, and tuberculosis (8).…”
Section: Epidemiology Of Rabies In Asia and Africamentioning
confidence: 99%
“…Males are more likely to develop rabies than females (the male/female ratio is 2.32:1). Farmers represent a high-risk population, accounting for 66.27% of all rabies cases in China, and rabies is most commonly seen in individuals between the ages of 5 and 15 years and 35 and 70 years (3,7). Canines (88.53% to 95.00%) remain the primary source of rabies infection in China, followed by cats (1% to 7%) (3, 9, 10), and Chinese ferret-badgers play an important role as a reservoir and in the transmission of rabies in the southeast of China (11).…”
Section: Epidemiology Of Rabies In Asia and Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Dog and animal bites are still a common problem in Thailand and in other canine endemic developing countries. Dog bites accounted for 5.3% of injuries in a major emergency room in Thailand [3], while animal bites were 0.3%−1% in other countries [4][5][6][7][8][9][10]. WHO has published guidelines for postexposure rabies vaccination [11].…”
Section: Brief Communication (Original)mentioning
confidence: 99%